Environment risk and impact assessment of the use of mercury for gold mining in the Santurban Paramo area, Colombia - Ortega -Ramirez, Angie Tatiana; Moreno, Daniela Garcia (International Journal of Sustainable Energy and Environmental Research, 2024)
Gold mining in the Santurban Paramo in Colombia contributes to the development and growth of the region by generating employment and income for the inhabitants. However, the benefits of this activity may be offset by the use of mercury in the amalgamation stage of gold production. Mercury is a heavy metal that is highly toxic and harmful to the health of people who are directly or indirectly involved in gold mining and causes damage to the environment, such as deterioration of vegetation cover, harmful effects to flora and fauna in the Paramo, disappearance of endemic species, and reduced quality of natural resources (water, soil, and air). This research seeks to analyze the different environmental impacts and risks of inadequate handling of mercury in gold mining. To do so, the mining activity process and the area of influence were first characterized and evaluated. Next, soil and air mercury concentrations were measured in the mining areas considered under this study. In the municipalities of California and Surata in the Santurban Paramo, values between 160– 226 g/t of mercury were measured in the production plants. Finally, the environmental impacts were evaluated with the help of an environmental risk matrix, obtaining higher risk indexes in natural resource quality and effects on flora and fauna of the Santurban Paramo.